The effects of chitosan oligosaccharides on OPG and RANKL expression in a rat osteoarthritis model - Zhang,Chun (2017)
Abstract Purpose: To investigate the effect of chitosan oligosaccharides (COS) against osteoarthritis (OA) and preliminarily discuss the osteoprotegerin (OPG), receptor activator of NF-κB ligand (RANKL) and RANK expression in a rat OA model. Methods: Thirty-six 6-week-old Male SD rats were randomly divided into three groups: sham-operated group(CON), OA-induction group(OA), COS intervention group(n=12/group). At 4 weeks after the operation, COS (50 ul) intervention weekily for consecutive 5 weeks. The OA and CON groups received an injection of 50 ul physiological saline. At death, 11 weeks following surgery, cartilage was harvested and total RNA and protein were extracted. Both the morphological changes of the cartilage were observed and harvested the total RNA and protein. Meanwhile, the expression of OPG, RANKL and RANK in cartilage were determined. Results: The expression of OPG and RANKL were both enhanced in the cartilage of the OA model. Compared with the OA group, COS treatment improved the cartilage damage (both extent and grade). Furthermore, the COS group showed highly OPG and lower RANKL. Simultaneously, COS treatment upregulated the ratio of OPG/RANKL and downregulated the RANKL/RANK. Conclusion: Chitosan oligosaccharides may be used as a unique biological agent to prevent and treat osteoarthritis, and this effect is associated with modulation of the expression of osteoprotegerin and receptor activator of NF-κB ligand.